Bibliometric Rankings of Journals based on the Thomson Reuters Citations Database - Chia-Lin Chang; Michael McAleer (Tinbergen Institute, 2015)
Virtually all rankings of journals are based on citations, including self citations by journals and individual academics. The gold standard for bibliometric rankings based on citations data is the widely-used Thomson Reuters Web of Science (2014) citations database, which publishes, among others, the celebrated Impact Factor. However, there are numerous bibliometric measures, also known as research assessment measures, based on the Thomson Reuters citations database, but they do not all seem to have been collected in a single source. The purpose of this paper is to present, define and compare the 16 most well-known Thomson Reuters bibliometric measures in a single source. It is important that the existing bibliometric measures be presented in any rankings papers as alternative bibliometric measures based on the Thomson Reuters citations database can and do produce different rankings, as has been documented in a number of papers in the bibliometrics literature.
Keywords: C18; C81; Y10; 330; Research assessment measures; Impact factors; Bibliometric measures